Stigma and posttraumatic growth among COVID-19 survivors during the first wave of the COVID-19 pandemic in Malaysia : a multicenter cross-sectional study - Nazirah, Azman; Nik Ruzyanei, Nik Jaafar; Mohammad Farris Iman Leong, Abdullah; Nur Iwana, Abdul Taib; Nurul Ain, Mohamad Kamal; Muhammad Najib, Abdullah; Siti Nordiana, Dollah; Mohd Shahrir, Mohamed Said (Frontiers Media S.A, 2023)
Background: Contracting COVID-19 can cause negative and distressing psychological sequelae, but traumatic stressors may also facilitate the development of positive psychological change beyond an individual’s previous level of adaptation, known as posttraumatic growth (PTG). As a result, studies have investigated the negative effects of COVID-19 on mental health, but data on PTG among patients who have recovered from COVID-19 remains limited. This study aims to evaluate the level of PTG and its associations with stigma, psychological complications, and sociodemographic factors among COVID-19 patients 6 months post-hospitalization.